Synaptic localization of kappa opioid receptors in guinea pig neostriatum. - Jomary, C (1992)
Distribution of kappa opioid receptors was examined by EM radioautography in sections of guinea pig neostriatum with the selective 125I-labeled dynorphin analog [D-Pro10]dynorphin-(1-11). Most specifically labeled binding sites were found by probability circle analysis to be associated with neuronal membrane appositions. Because of limitations in resolution of the method, the radioactive sources could not be ascribed directly to either one of the apposed plasma membranes. Nevertheless, three lines of evidence favored a predominant association of ligand with dendrites of intrinsic striatal neurons: (i) the high frequency with which labeled interfaces implicated a dendrite, (ii) the enrichment of dendro-dendritic interfaces, and (iii) the occurrence of dendritic profiles labeled at several contact points along their plasma membranes. A small proportion of labeled sites was associated with axo-axonic interfaces, which may subserve the kappa opioid-induced regulation of presynaptic dopamine and acetylcholine release documented in guinea pig neostriatum. Although most membrane-associated kappa sites were found at extrasynaptic locations, approximately 23% were associated with synaptic specializations. This proportion is markedly higher than that previously reported for either mu or delta sites in rat neostriatum. Whether labeled synapses represent preferential sites of action for kappa ligands remains to be established. In any event, these results support the hypothesis that in mammalian brain kappa opioid receptors are conformationally and functionally distinct from mu and delta types.